2003
DOI: 10.1021/ie0340185
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Valuable Tea Aroma Components by Pervaporation

Abstract: The present work describes the possibility of using pervaporation to recover the tea aroma compounds from tea aroma condensate generated in the manufacturing of tea or instant tea, as well as directly from tea extract. Eight compounds that make a significant contribution to tea aroma, namely, trans-2-hexenal, linalool, cis-3-hexenol, 3-methylbutanal, 2-methylpropanal, benzyl alcohol, phenylacetaldehyde, and β-ionone, were studied in this work. Permeation studies for all of these compounds with poly(octyl methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 15 publications
(19 reference statements)
1
28
0
Order By: Relevance
“…Sampranpiboon et al (2000) also compared PDMS and POMS membranes for pervaporation of aqueous ethyl butanoate and ethyl hexanoate, and found that both membranes had similar ester fluxes, but that the POMS membrane had a higher separation factor because its water flux was lower. Kanani et al (2003) obtained greater separation factors with POMS membranes than with PDMS membranes for some tea aroma compounds such as linalool and cis-3-hexenol. However, PDMS membranes gave better separation factors for aldehydes and some other compounds.…”
Section: Effect Of Membrane Type On Total and Individual Fluxmentioning
confidence: 92%
See 3 more Smart Citations
“…Sampranpiboon et al (2000) also compared PDMS and POMS membranes for pervaporation of aqueous ethyl butanoate and ethyl hexanoate, and found that both membranes had similar ester fluxes, but that the POMS membrane had a higher separation factor because its water flux was lower. Kanani et al (2003) obtained greater separation factors with POMS membranes than with PDMS membranes for some tea aroma compounds such as linalool and cis-3-hexenol. However, PDMS membranes gave better separation factors for aldehydes and some other compounds.…”
Section: Effect Of Membrane Type On Total and Individual Fluxmentioning
confidence: 92%
“…POMS is more hydrophobic than PDMS because of its larger side group (Fig. 2) (Kanani et al, 2003;Trifunovic´& Tra¨ga˚rdh, 2006). Sampranpiboon et al (2000) also compared PDMS and POMS membranes for pervaporation of aqueous ethyl butanoate and ethyl hexanoate, and found that both membranes had similar ester fluxes, but that the POMS membrane had a higher separation factor because its water flux was lower.…”
Section: Effect Of Membrane Type On Total and Individual Fluxmentioning
confidence: 99%
See 2 more Smart Citations
“…As analytes pass through the membrane, a change in volume makes the membrane more permeable, but obviously less selective, until reaching an unacceptable selectivity, and the membrane must be regenerated. Typical applications are the recovery and determination of volatile aroma compounds in fruit juice processing, [65][66][67] those that make a significant contribution to tea aroma, 68 wine, 69 or natural aroma compounds. 70 Due to different affinity for the membrane and different diffusion rate, a component at low concentration in the feed can be highly enriched in the permeate.…”
Section: Nonporous Polymeric Membrane Extractionmentioning
confidence: 99%